The Maya Landscape of El Infiernito, Chiapas, Mexico: Comparison of Occupied and Unoccupied Airborne LiDAR Mapping Systems - Whittaker Schroder; Timothy Murtha; Andrew K. Scherer; Shanti Morell-Hart; Charles Golden; Eben N. Broadbent; Angélica M. Almeyda Zambrano; Juan Carlos Fernandez-Diaz (Remote Sensing)
Landscape-oriented approaches in archaeology have moved beyond site-based research to interpret how people have engaged with, modified, and constructed the environment and how the legacies of these activities continue to influence land use. In the Maya Lowlands, landscape archaeology is related to the analysis of settlement patterns, households, agricultural intensification, and water management. The increasing availability of LiDAR data has revolutionized the mapping of archaeological landscapes under vegetation, especially in tropical environments like the Maya Lowlands, but researchers still emphasize site-oriented settlement densities and infrastructure. Furthermore, the accessibility of drone-based LiDAR platforms has the potential to collect data across several seasons or years to facilitate change detection. In this paper, we compare three LiDAR datasets collected from 2018 to 2023, using both occupied and unoccupied airborne systems. The landscape surrounding the archaeological site of El Infiernito, Chiapas, Mexico near the Classic period (AD 250–800) dynastic capital of Piedras Negras, Guatemala was selected to compare these LiDAR datasets in the context of prior, extensive ground-based fieldwork. These data were used to interpret the built environment, land use, hydrology, landscapes of movement, and other infrastructure constructed and modified by several communities beginning in the Late Preclassic period (400 BC–AD 250) to the present. When used alongside systematic survey and ground verification, the combination of several LiDAR platforms to collect data across different seasons at El Infiernito enhanced the understanding of the spatial distribution of archaeological sites and features across the karst landscape.